Parasympathetic neurons in the human submandibular ganglion. (June 2021) - Kawashima, Mutsuko; Yajima, Takehiro; Tachiya, Daisuke; Kokubun, Souichi; Ichikawa, Hiroyuki; Sato, Tadasu
Highlights: Human submandibular ganglion has parasympathetic postganglionic neurons. These neurons contained VIP, ChAT, DBH and TRPV2. Pericellular nerve fibers had VIP, DBH and TRPV2. Perivascular nerve fibers in submandibular gland contained TRPV1 and TRPV2. TRPV2-positive nerve fibers were located close to myoepithelial and acinar cells. Abstract: The submandibular ganglion (SMG) contains parasympathetic neurons which innervate the submandibular gland. In this study, immunohistochemistry for vasoactive intestinal polypeptide (VIP), neuropeptide Y (NPY), choline acetyltransferase (ChAT), dopamine β-hydroxylase (DBH), tyrosine hydroxylase (TH), and the transient receptor potential cation channel subfamily V members 1 (TRPV1) and 2 (TRPV2) was performed on the human SMG. In the SMG, 17.5 % and 8.9 % of parasympathetic neurons were immunoreactive for VIP and TRPV2, respectively. SMG neurons mostly contained ChAT- and DBH-immunoreactivity. In addition, subpopulations of SMG neurons were surrounded by VIP (69.6 %)-, TRPV2 (54.4 %)- and DBH (9.5 %)-immunoreactive (-ir) nerve fibers. SMG neurons with pericellular VIP- and TRPV2-ir nerve fibers were significantly larger than VIP- and TRPV2-ir SMG neurons, respectively. Other neurochemical substances were rare in the SMG. In the human submandibular gland, TRPV1- and TRPV2-ir nerve fiber profiles were seen around blood vessels. Double fluorescence method also demonstrated that TRPV2-ir nerve fiber profiles were located around myoepithelial and acinar cells in the submandibular gland. VIP and TRPV2 are probably expressed by both pre- and post-ganglionic neurons innervating the submandibular and sublingual glands. VIP, DBH and TRPV2 may have functions about regulation of salivary components in the salivary glands and neuronal activity in the SMG.